KEPEMILIKAN MANAJERIAL, DEWAN KOMISARIS, PROFITABILITAS, DAN STRUKTUR MODAL - Tyara Dwi Putri (ITB AAS INDONESIA Surakarta, 2022)
This study aims to analyze the effect of managerial ownership, board of commissioners, and profitability on capital structure. The sample used in this study were 23 companies with a total of 92 observations. The results showed that managerial ownership and profitability had no effect on capital structure. The board of commissioners has a negative and significant effect on the capital structure. The control variable, namely the size of the company has a negative and significant effect on the capital structure. While the age of the company does not affect the capital structure. Keywords: Managerial Ownership, Board of Commisioners, Profitability, Capital Structures